Applying a reservoir functional-zone paradigm to littoral bluegills: differences in length and catch frequency? - Nathan Ruhl; Holly DeAngelis; Abigale M. Crosby; Willem M. Roosenburg (PeerJ, 2014)
Reservoirs exhibit gradients in conditions and resources along the transition from lotic to lentic habitat that may be important to bluegill ecology. The lotic–lentic gradient can be partitioned into three functional zones: the riverine, transitional, and lacustrine zones. We measured catch frequency and length of bluegills (Lepomis macrochirus) captured along the periphery of these areas (i.e., in the littoral zone of each functional zone) for four small reservoirs in Southeastern Ohio during the summer months of three years. Catch frequency differed between zones for two reservoirs, but these differences were not observed in other years. There was no relationship between reservoir zone and either standard length or catch frequency when the data for all reservoirs were pooled, but we did observe a bimodal length distribution in all reservoirs. A combination of ecological factors including inter and intraspecific competition, predation intensity, management practices, limnology, and assemblage complexity may be mitigating bluegill distribution and abundance in reservoirs. Therefore, a functional zone (categorical) approach to understanding bluegill ecology in reservoirs may not be appropriate.